UMP appreciates pensioners, encourages them to share expertise and skills - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 16 December 2022 - The Vice-Chancellor of Universiti Malaysia Pahang (UMP), Professor Dato’ Ts. Dr. Yusserrie Zainuddin encouraged UMP retirees to use all the skills, expertise and experience gained while serving the university to continue contributing to the community.